Audit mandates, audit firms, and auditors - Matthias Breuer; Anthony Le; Felix Vetter (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2023)
Audits by private, third-party auditors are frequently mandated to ensure compliance with regulations (e.g., accounting or environmental standards). We examine how such mandates shape the market for audits. In our empirical examination, we focus on one of the oldest and most prominent audit markets, the market for audits of firms' financial accounting. Using novel data on firms, audit firms, and auditors-the key players in the market-, we find that audit mandates increase the number of audits, audit firms, and auditors, but decrease average auditor wages. These findings are consistent with mandates creating demand for low-quality audits, originating from involuntarily audited firms, in a market with differentiated audit qualities. In line with this interpretation, we find that the regulatory audit demand emanates from smaller firms with limited incentives to obtain audits voluntarily; and is served by smaller audit firms and less experienced auditors. Collectively, our findings suggest that the promise of audit mandates as a means to ensure regulatory compliance may be limited by the emergence of low-quality audits.
Keywords: G18; G38; J23; J24; J31; J42; K22; L10; L51; L84; M42; M48; 330; Auditing; Mandates; Employees; Wages; Quality; Market Structure